Pengaruh ROA, NPL, BOPO & SBI Terhadap Penyaluran Kredit Bank Pemerintah Dan Bank Asing - Rachi Titi Komalasari (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
The research objective was to determine the effect Return on Assets (ROA) ratio, Operational Costs to Operating Income (BOPO), Non Performing Loans (NPL), and Sertificate Bank Of Indonesia (SBI) towards lending to Goverment Banks and Foreign Bank. The independent variable consists of ROA, BOPO, NPL and SBI while the dependent variable is credit distribution. The population in this study are 4 Goverment Banks and 9 Foreign Bank. The sampling method uses purposive sampling with a sample of 13 banks in accordance with certain criteria. Data analysis method uses linear multiple regression with calculations using the SPSS program. The results showed that ROA, BOPO, NPL and SBI had a negative and significant effect on credit distribution.